E-Learning Dalam Pembelajaran Pendidikan Agama Islam - Muhammad Eka Mahmud (Universitas Nurul Jadid Paiton Probolinggo, East Java, 2019)
The era of information communication and technology supported by a power of information and communication technology has major implications in everyday human life, such as how to work and manage organizations (including educational institutions) as well as ways of looking at the outside world. Thus, interactions between individuals, organizations, communities and countries can be carried out without being hindered by space, time and integrated into this global communication network. Developing e-learning is managing cultural change, values, and ways of communicating and interacting in building education and students through learning. Strategic steps taken to get to e-learning are the formation of a bureau that works to accelerate the functioning e-learning program; working to simplify operational technical matters relating to the digital world, it works to support all operational difficulties becomes easy. All data related to school can be accessed easily including learning